A Global Approach to Control Nosocomial Infections in a Large General Teaching Hospital - Gordets, Bart; Heyneman, Bea; Jannes, Hilde; Lenez, Aline (International Journal of Infection Control, 2007)
An increase in nosocomial infections with multi-resistant bacteria prompted the infection control team at Sint Jan General Hospital to adopt a new hospital-wide strategy involving implementation of the VigiGerme® infection prevention and control model. Improvement in attitudes and perceptions of nosocomial infections has resulted in demonstrable reductions in the incidence of methicillin-resistant Staphylococcus aureus (MRSA) and quinolone-resistant Enterobacter aerogenes (QREA) infections.